2012
DOI: 10.1016/j.ejvs.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Matrix Metalloproteinase-9: A Possible Diagnostic Marker of Successful Endovascular Aneurysm Repair

Abstract: Plasma MMP-9 levels appear to discriminate between patients with and without an endoleak with high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 5 publications
0
52
2
2
Order By: Relevance
“…Monaco et al, 25 for example, specifically investigated endoleaks after EVAR for descending thoracic aortic aneurysm compared with AAA in this study, and pathophysiologic differences may complicate direct comparison of their findings and ours. Sample sizes used in this study were larger than those of the previous reports that assessed MMP9 in AAA patients with endoleak, 24,[26][27][28] suggesting greater analytical power, although further studies employing large cohorts of patients are needed to more definitively assess the 20,[29][30][31] attributable in part to the formation of a large nonocclusive thrombus within the aneurysmal sac. 32 Surprisingly, the association of plasma D-dimer concentration with endoleak has been directly examined only in a single study, which reported that circulating D-dimer concentrations were significantly higher in patients suffering type I endoleak (compared with nonendoleak controls) and were highly diagnostic for type I endoleak after ROC analysis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Monaco et al, 25 for example, specifically investigated endoleaks after EVAR for descending thoracic aortic aneurysm compared with AAA in this study, and pathophysiologic differences may complicate direct comparison of their findings and ours. Sample sizes used in this study were larger than those of the previous reports that assessed MMP9 in AAA patients with endoleak, 24,[26][27][28] suggesting greater analytical power, although further studies employing large cohorts of patients are needed to more definitively assess the 20,[29][30][31] attributable in part to the formation of a large nonocclusive thrombus within the aneurysmal sac. 32 Surprisingly, the association of plasma D-dimer concentration with endoleak has been directly examined only in a single study, which reported that circulating D-dimer concentrations were significantly higher in patients suffering type I endoleak (compared with nonendoleak controls) and were highly diagnostic for type I endoleak after ROC analysis.…”
Section: Discussionmentioning
confidence: 94%
“…10 Several prior investigations have assessed the relationship between circulating MMP9 concentrations and endoleak presence, although the significance and extent of the reported associations vary between studies. [24][25][26][27][28] A recent meta-analysis of these studies identified a significant positive association of plasma MMP9 concentration with endoleak presence. 10 The findings of that meta-analysis are contradicted by those of this study as no relationship between endoleak diagnosis and circulating MMP9 concentration was observed.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the thoracic aorta, measurement of circulating MMP-9 has been shown to correlate to aortic root dilatation. 17 Interestingly, elevated plasma MMP-9 levels have been used to predict endoleaks after endovascular therapy of the abdominal 18 and thoracic 19 aorta. The present work supports the above results and establishes preliminary algorithms for the screening of patients for ascending aortic aneurysm disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among EVAR patients, those with endoleak have significantly higher levels of plasma MMP-9 levels than those without endoleak (89.54 ± 26.46 vs 25.02 ± 13.40 ng/ml; p < 0.001). Regression analysis showed no significant influence of age, sex and AAA sizes [87]. In a population-based study from the Dallas Heart Study, higher plasma MMP-9 levels independently associated with higher aortic wall thickness (p < 0.0001) and larger luminal diameter (p < 0.0001) [88].…”
Section: Association Of Circulating Mmps With Human Aaasmentioning
confidence: 99%